Performance Evaluation of Short Packet Communications in NOMA VLC Systems With Imperfect CSI - Giang N. Tran (IEEE Access, 2022)
In this paper, we analyze and evaluate the impacts of imperfect channel state information (CSI) of the short packet communication (SPC) in a non-orthogonal multiple access (NOMA) visible light communication (VLC) system. We consider a downlink NOMA VLC system, in which one light emitting diode (LED) serves two single-photodiode users with the channel estimation error. To this end, we derive the closed-form expression for the block error rate (BLER) with imperfect CSI by using a Gaussian Chebyshev quadrature method, from which the expressions of reliability, latency, and throughput are carried out. Then, we compare the performance of the SPC in the NOMA VLC system to that of the OMA VLC system. The results show that the SPC-NOMA VLC system outperforms the SPC-OMA VLC system for all power allocation strategies and channel estimation errors. We examine the impact of the imperfect successive interference cancellation (SIC) at a near user and the impact of choosing LED semi-angle on the system throughput. Furthermore, we use the functional-iteration-based one-dimensional search method to get maximum throughput at the near user while guaranteeing a certain throughput at the far user.